EF-Tu and EF-G are activated by allosteric effects - Mondal, Dibyendu (Proc Natl Acad Sci U S A, 2018)
Many cellular processes are controlled by GTPases, and gaining quantitative understanding of the activation of such processes has been a major challenge. In particular, it is crucial to obtain reliable free-energy surfaces for the relevant reaction paths both in solution and in GTPases active sites. Here, we revisit the energetics of the activation of EF-G and EF-Tu by the ribosome and explore the nature of the catalysis of the GTPase reaction. The comparison of EF-Tu to EF-G allows us to explore the impact of possible problems with the available structure of EF-Tu. Additionally, mutational effects are used for a careful validation of the emerging conclusions. It is found that the reaction may proceed by both a two-water mechanism and a one-water (GTP as a base) mechanism. However, in both cases, the activation involves a structural allosteric effect, which is likely to be a general-activation mechanism for all GTPases.